Fenologia de uma comunidade arbórea em Santa Maria, RS - Alberti, Luis Fernando (2002)
This work aimed to describe the reproductive (flowering and fruiting) and vegetative (leaf change) phenological events of a Seasonal Deciduous Forest tree community located in Santa Maria county (53°50' W long. and 29°37' S lat.), Rio Grande do Sul State, Brazil relating them to the main climatic variables (temperature, rainfall, and day length) registered during the study period and with the climatic variables means of 1990 to 2000 period. Between June 2000 and June 2001 the phenology of 407 tree individuals located on Cerrito Hill (individuals large than 10 cm DBH) and Tabor Hill (individuals large than 30 cm DBH) was monitored each 14 days. All the main studied phenophases showed great sazonality. Leaf change as well as flowering occured on the transition between the brief dry to the rainy season. Leaf fall occured in the end of the dry season. Fruiting showed lower degree of seasonality in relation to flowering with individuals fruiting all year round. The majority of climatic variables correlated significantly with the phenophases both with the study period data as well as with the 10 years mean period data. The rainfall had the best correlation with the phenophases when it was used the mean of 10 years period of climatic data. On the whole the flowering and leaf budding were induced by the elevation on rainfall, temperature and day length hours occured along September. Fruiting is correlated only with the two first variables mentioned above. Leaf fall is correlated to the low temperature occured during the winter months, together with the low values of rainfall and day length. The present results corroborate the influence of abiotic factors on phenophase induction on geographic regions relatively far away from Equator line.